Criminal Prosecution for Organizing or Maintaining Dens for the Consumption of Narcotic Drugs, Psychotropic Substances, Their Analogues and Providing Premises for The Same Purposes Under the Legislation of the Republic of Kazakhstan - Umerzhanovich, Seytkhozhin Bulat; Khalelovich, Fetkulov Alikzhan; Vladimirovna, Sidorova Natalya; Sericbaevna, Togaibaeva Sholpan; Habilovna, Satbaeva Kuralay; Sabitovich, Orynbekov Almas (International Journal of Criminology and Sociology, 2022)
The main aim of the study is to consider problematic issues related to the qualification of a criminal offense, provided for in Article 302 of the Criminal Code of the Republic of Kazakhstan “Organization or maintenance of dens for the consumption of narcotic drugs, psychotropic substances, their analogues and the provision of premises for the same purposes”. This article describes the circumstances that make it difficult to prosecute persons who provide their homes or other premises for the consumption of narcotic drugs, psychotropic substances, their analogues, as well as the organizers of this type of illegal activity, creating conditions for anesthesia of the population. Through the study and analysis of statistical information, available approaches to this issue, as well as materials of judicial investigative practice in cases of this category, an attempt was made to consider the causes and conditions conducive to the commission of this offense, an author’s vision of resolving the situation was proposed. The article presents the data of criminal statistics in Kazakhstan for 2015-2018, identifies the most typical conditions conducive to the creation and functioning of drug traffickers, makes reasonable proposals for amending Article 302 of the Criminal Code of the Republic of Kazakhstan, aimed at improving the current criminal law. The materials of the article can be of practical value for law enforcement officers fighting the specified type of crime.